(untitled) (Innovative professional education, 2022)
The preparation of applicants for higher education for degree of PhD in scientific institutions involves the acquisition of theoretical knowledge, skills and other competencies sufficient to produce new ideas, solve complex problems in the field of professionaland research and innovation activities, master the methodology of scientific and pedagogical activities, and also conduct their own scientific research, the results of which are of scientific novelty, theoretical and practical significance.